Difference in the level of complexity assessed on patients with advanced cancer referred to a hospital-based palliative care unit by multidisciplinary teams and wards: a retrospective study - Silvia Tanzi; Carlo Peruselli; Sara Alquati; Carlotta Pellegri; Simona Sacchi (BMC Health Services Research)
Abstract Background The main criterion for the intervention of specialist palliative care is how to balance complexity of needs and prognosis. Appropriate organization and dedicated clinical tools should enable the clinicians and patients to meet this criterion. Methods We conducted a retrospective observational study on 184 cancer patients referred to a specialized palliative care service. The difference in level of complexity was analyzed using the PALCOM scale assessment tool in regard to referrals from multidisciplinary teams versus wards. A specialized palliative care service trained the health professionals of the multidisciplinary teams in 2019 and has been working daily in the hospital since 2013. Results The number of referrals to the palliative care service by the wards was more than double the referrals by the multidisciplinary teams, and the level of complexity was 45% for patients referred by wards vs. 10% referred by discussion teams. From our results, it seems reasonable to assume that training in complexity tools may increase the number of referrals to the palliative care service, while working alongside the health professionals in the wards leads to an increase in recognizing complex needs and thus better appropriateness of referrals to the palliative care service. Conclusions A hospital-based specialist palliative care service with clinical and training expertise can increase the appropriateness of referrals.